2022
DOI: 10.3389/fnut.2022.819722
|View full text |Cite
|
Sign up to set email alerts
|

Coated Zinc Oxide Improves Growth Performance of Weaned Piglets via Gut Microbiota

Abstract: Weaned piglets stayed in transitional stages of internal organ development and external environment change. The dual stresses commonly caused intestinal disorders followed by damaged growth performance and severe diarrhea. High dose of zinc oxide could improve production efficiency and alleviate disease status whereas caused serious environmental pollution. This research investigated if coated ZnO (C_ZnO) in low dose could replace the traditional dose of ZnO to improve the growth performance, intestinal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 51 publications
3
15
1
Order By: Relevance
“…Liu et al also reported that early supplementation with ZnO increased the relative abundances of Subdoligranulum compared with the CON group in pre-weaned dairy calves [51]. ZnO treatment raised the abundance of Intestinibacter [6], which was in line with our study. Another study demonstrated that two alternatives' addition in dairy cows improved immune functions and the relative abundances of Lachnospiraceae, Monoglobaceae and Butyricicoccaceae in their feces [52], whereas our results showed that Zn supplementation enhanced the activities of antioxidant enzymes, but reduced the relative proportions of Butyricicoccaceae, Monoglobaceae and Lachnospiraceae.…”
Section: Discussionsupporting
confidence: 91%
“…Liu et al also reported that early supplementation with ZnO increased the relative abundances of Subdoligranulum compared with the CON group in pre-weaned dairy calves [51]. ZnO treatment raised the abundance of Intestinibacter [6], which was in line with our study. Another study demonstrated that two alternatives' addition in dairy cows improved immune functions and the relative abundances of Lachnospiraceae, Monoglobaceae and Butyricicoccaceae in their feces [52], whereas our results showed that Zn supplementation enhanced the activities of antioxidant enzymes, but reduced the relative proportions of Butyricicoccaceae, Monoglobaceae and Lachnospiraceae.…”
Section: Discussionsupporting
confidence: 91%
“…Lactobacillus is a probiotic that improves gut health via a range of routes, including pathogen suppression, immunological regulation, and inflammation reduction. 17 In the present investigation, the population of Lactobacillus was significantly increased in feces, possibly because polysaccharides in the yeast cell wall stimulate the proliferation of Lactobacillus in the intestine. Moreover, lactic acid, the primary metabolite of Lactobacillus , has a crucial function in the proliferation of intestinal stem cells, which might mitigate the negative effects of stress-induced intestinal damage on the host.…”
Section: Discussionmentioning
confidence: 45%
“…The diarrhea incidence of piglets was recorded based on a pen following the previous report in this trial. 17 About 300 g fecal samples from each pen were collected on days 25, 26 and 27 of the trial, and then each pen's fecal samples were mixed up before drying. All experimental diets and fecal samples were placed in an oven, gradually heated up to 65 °C for 72 h and then smashed to pass through a 1.0 mm mesh screen for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…But the villi height of the ileum was decreased in ZnO + CT group, compared with ZnO group. In addition, previous studies have shown that coated ZnO can improve ileum villus height ( Sun et al, 2022 ). This may be due to the interaction between ZnO and CT. Liu et al found that hydrolyzed tannin increased the villus height of ileum, which was inconsistent with our results.…”
Section: Discussionmentioning
confidence: 99%